2009
DOI: 10.1002/jmri.21875
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of diffusion‐weighted MRI for defining placental invasion

Abstract: The purpose of this clinical note is to describe the feasibility of using diffusion‐weighted imaging for diagnosing placental invasion with a case of placenta increta and six cases without it. Diffusion‐weighted imaging (DWI) at a b‐value of 1000 sec/mm2 can clearly define the border between the placenta and myometrium because only the placenta shows very high signal intensity. The corresponding image at a b‐value of 0 sec/mm2 shows the myometrium with high signal intensity compared with the surrounding fat. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…Two additional studies report high accuracy for the detection of pelvic dissemination of gynecologic malignancy (16) and of myometrial invasion of endometrial cancer (17) by means of the use of fusion of T2WI and DWI, although neither study presents data regarding the performance of DWI viewed either alone or in conjunction with T2WI but without fusion. Also, fusion of DWI obtained using b-values of 0 s/mm 2 and of 1000 s/mm 2 (with the former image essentially representing a T2-weighted image) has been described as useful for detection of placental invasion in a cases series that contained three positive and four negative cases (18). Finally, a study that assessed the utility of DWI for characterization of pelvic lymph nodes in patients with prostate cancer states that T2WI and DWI were fused during image analysis to assist with anatomic localization (19), and a study that assessed the utility of DWI for prediction of seminal vesicle invasion in patients with prostate cancer shows fused T2WI and DWI in its Figures (20).…”
Section: Discussionmentioning
confidence: 99%
“…Two additional studies report high accuracy for the detection of pelvic dissemination of gynecologic malignancy (16) and of myometrial invasion of endometrial cancer (17) by means of the use of fusion of T2WI and DWI, although neither study presents data regarding the performance of DWI viewed either alone or in conjunction with T2WI but without fusion. Also, fusion of DWI obtained using b-values of 0 s/mm 2 and of 1000 s/mm 2 (with the former image essentially representing a T2-weighted image) has been described as useful for detection of placental invasion in a cases series that contained three positive and four negative cases (18). Finally, a study that assessed the utility of DWI for characterization of pelvic lymph nodes in patients with prostate cancer states that T2WI and DWI were fused during image analysis to assist with anatomic localization (19), and a study that assessed the utility of DWI for prediction of seminal vesicle invasion in patients with prostate cancer shows fused T2WI and DWI in its Figures (20).…”
Section: Discussionmentioning
confidence: 99%
“…Leyendecker and colleagues 2 agreed that these sequences reasonably differentiate between the placenta and myometrium, but available evidence suggests that it is difficult in practice. 2,33 Morita and co-workers 34 suggested that diffusionweighted (DW) sequences seems promising in evaluation of invasive placenta. 34 They reported that in DW images the placenta at a b-value of 1000 sec/mm 3 shows very high signal intensity, which enables clear identification of the placentaemyometrium interface.…”
Section: Nsa Rahaim Eh Whitby / Clinical Radiology XXX (2015) Ementioning
confidence: 99%
“…2,33 Morita and co-workers 34 suggested that diffusionweighted (DW) sequences seems promising in evaluation of invasive placenta. 34 They reported that in DW images the placenta at a b-value of 1000 sec/mm 3 shows very high signal intensity, which enables clear identification of the placentaemyometrium interface. The myometrium at a bvalue of 0 sec/mm 3 likewise shows very high signal intensity, which makes it distinctive from the surrounding fat.…”
Section: Nsa Rahaim Eh Whitby / Clinical Radiology XXX (2015) Ementioning
confidence: 99%
“…As GBCA remain relatively contraindicated in pregnancy [29], several investigators have evaluated DWI for characterization of these pathologies. In a feasibility study examining DWI in placental invasion, Morita et al described improved tissue contrast between the placenta and myometrium with DWI over conventional pulse sequences and clear depiction of a case of placenta increta, though placenta accreta was not well depicted [30]. Masselli et al, reporting on a series of 19 cases of placental abruption, found 53% sensitivity with US, 95% sensitivity with T1-WI, and 100% sensitivity with DWI in making the diagnosis of abruption.…”
Section: Placental Abnormalitiesmentioning
confidence: 96%